Early diagnosis and successful treatment of cytomegalovirus peritonitis in children with primary nephrotic syndrome: case series and literature review. Issue 1 (1st January 2020) - Lin, Haiting; Chen, Lizhi; Wen, Songyang; Yue, Zhihui; Mo, Ying; Jiang, Xiaoyun; Huang, Liuyi
Abstract: Cytomegalovirus (CMV) is a major pathogen in immunocompromised population and CMV infections in immunocompromised patients cause substantial morbidity and mortality. The common clinical manifestations of CMV infection are pneumonia, hepatitis, colitis and so on, while CMV peritonitis without gut perforation is rare. Reviewing the literature, CMV peritonitis in patients with nephrotic syndrome (NS) had not been reported. Only four cases of CMV peritonitis without gut perforation were reported in adults with other diseases. Two cases were diagnosed by reverse-transcription polymerase chain reaction (RT-PCR) of ascites while the other two cases by histopathological examination of peritoneal tissue. We report four cases of primary nephrotic syndrome complicated with CMV peritonitis. Four cases all diagnosed by RT-PCR of ascites (659–455 000 copies/mL). We mainly discusses the diagnosis and treatment of CMV peritonitis without gut perforation.